To study the antihyperglycaemic and lipid lowering effect of garlic as an adjunct to metformin in patients of type 2 diabetes mellitus with obesity - Chhatwal, Simran; Sharma, Rahat Kumar; Sharma, Geeta; Khurana, Ashok (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus is a metabolic disorder of multiple aetiology characterized by chronic hyperglycaemia associated with disturbances of carbohydrate, fat and protein metabolism. The treatment constitutes lifestyle management, exercise, weight control and antihyperglycaemic drugs like sulfonylureas, biguanides, alpha-glucosidase inhibitors, thiazolidinediones, and meglitinide. Garlic has shown to have anti-hyperglycaemic and lipid lowering effects in various animal and human studies. Thus, this study was conducted to assess the antihyperglycaemic and lipid-lowering properties of Garlic in type2 diabetes patients with obesity. Methods: This was an open labelled prospective comparative study conducted on Type 2 diabetes mellitus patients with obesity where a total of 60 patients divided into two groups of 30 each (of either sex) were enrolled. Group 1 was given Tab. metformin 500mg BD/TDS after meals. Group 2 was given Tab. metformin in a dose of 500mg BD/TDS after meals along with Cap. Garlic (Allium sativum) 250mg BD. Patients were routinely investigated for fasting blood sugar, HbA1c and lipid profile i.e. Serum Cholesterol, HDL-C, Triglycerides and LDL-C at the start of the study. Patients were followed up at an interval of two weeks upto 12 weeks. Data obtained at the end of the study was statistically analysed using Student’s –t test. Results: It was observed that both metformin and garlic reduced FBG and HbA1c significantly but percentage reduction in FBG was more with garlic but, change in HbA1c was not significant. Fall in total CHL, TG, LDL and an increase in HDL were more pronounced in patients treated with Garlic when given along with Metformin. Conclusions: Therefore, garlic showed better results as an antihyperglycaemic and lipid lowering agent.